A limited anodic and cathodic potential window of MoS2: limitations in electrochemical applications. Issue 7 (22nd January 2015) - Nasir, Muhammad Zafir Mohamad; Sofer, Zdenek; Ambrosi, Adriano; Pumera, Martin
Abstract : MoS2 exhibits the limited potential windows in the anodic and cathodic regions due to the inherent electrochemistry and catalytic hydrogen evolution. Abstract : Molybdenum disulphide has been touted as a good material with diverse possible applications such as an energy storage and sensing platform. However, we demonstrate here the limitation of MoS2 as an analytical sensing platform due to the limited potential window in both the anodic and cathodic regions attributed to the inherent electrochemistry (oxidation of Mo 4+ to Mo 6+ ) and the catalytic hydrogen evolution reaction due to H3 O + reduction on the MoS2 surface, respectively. The electrochemical window of MoS2 lies in the region of ∼–0.6 V to +0.7 V ( vs . AgCl). We show that such a limited working potential window characteristic of MoS2 precludes the detection of important analytes such as nitroaromatic explosives, pesticides and mycotoxins which are instead detectable on carbon surfaces. The limited potential window of MoS2 has to be taken into consideration in the construction of electroanalytical devices based on MoS2 .